Monitoring mosaic biotopes in a marine conservation zone by autonomous underwater vehicle - Benoist, Noëlie M A (Conservation biology : the journal of the Society for Conservation Biology, 2019)
© 2019 The Authors. Conservation Biology published by Wiley Periodicals, Inc. on behalf of Society for Conservation Biology.